The transformation of academic ideals: an Australian analysis. Issue 5 (2nd September 2016) - Cannizzo, Fabian
ABSTRACT: This article explores the role that universities play in shaping the relationship between academics and their work. Drawing on Miller and Rose's interpretation of our present era as being characterised by 'Advanced Liberal' governance, this article demonstrates how discourses seeking to govern academic labour enrol ideals about the academic and subjectify academic staff within strategies to govern their conduct. Entrepreneurial conceptions of 'good' academic conduct are valorised through such initiatives as performance evaluation, interdisciplinary research programmes and Graduate Certificates of university teaching and skills development. Drawing on the past literature and an analysis of three Australian public universities, this article proposes three ideals through which academics are enrolled into strategies to govern their conduct: 'the career academic', 'the tribal academic' and 'the celebrity academic'. The centrality of an entrepreneurial sense of self within academic ideals contributes to the production of insidious effects within academic practices. The subjectification of academics, as entrepreneurial knowledge managers, may potentially produce strain within academics who fail to close the psychological distance between their self-perceptions and academic ideals. This article proposes that future investigations of the development of academic ideals and values should engage with an analysis of modes of self-government. The utility of self-government is explored in an analysis of the dynamic production of academic ideals within policies and programmes aimed at governing the behaviour of academic staff.